A practical review of the evolution of international reporting standards for mineral resources and mineral reserves - Glaucia Cuchierato; Ana Carolina Chieregati; Yuri Fernando Parra Castilho; Gabriela Cardoso Prado (REM: International Engineering Journal)
Abstract The purpose of this article is to show the evolution of international reporting standards for the public reporting of exploration results, mineral resources, and reserves, from the first initiatives to the current days. Particularities, similarities, and components, which ensure that the information provided complies to various worldwide instruments, are discussed. We also examined the recent changes in the national/regional Codes and guides, including the CRIRSCO Template published in late 2019. The systematization promotes understanding of company risks from the capital market and other financing mechanisms, making it possible to compare projects and do benchmarking analysis, allowing mining companies to comply in a more efficient, transparent, and less costly way to the jurisdictions under which they operate. Finally, presented is a chronology and evolution of the standardization and the localization of similar topics within the Codes of the CRIRSCO Family. The international reporting standards are a relevant and consistent instrument with reliable statements, clear language, and are recognized from one jurisdiction to another by financial institutions, which helps to improve and increase confidence in the mining industry. The objective of the CRIRSCO members is to provide and promote the understanding of the practices for mining investment decisions, being successful around the world.